Morfološke razlike izmeðu skupina prvoligaških odbojkaša razlicitih pozicija u igri - Durkovic, T.; Marelic, N.; Resetar, N. (Croatian Sports Medicine Journal, 2012)
Regard to specificity of volleyball game considerable effect of certain morphological characteristics on the success of the game is logical. Using morphological anthropometry it is possible to collect informations for primary selection of candidates for volleyball, but also informations that could be used in the secondary selection - so called specialization. Specialization determinates specific playing roles with specific assignments for each player. Assignments are typical for each playing role so the importances of certain morphological measures are different. The aim of this study was to examine the positional differences in the area of anthropometric characteristics of Croatian and Slovenian premier league volleyball players. The research was conducted on a 60 senior volleyball players all members of Croatian and Slovenian premier league. Players were categorized as setters (n=9), receivers - attackers (n=16), diagonal players - correctors (n=16), central players (n = 13) and liberos (n=6). The sample of variables consisted of 27 anthropometric measures all taken following the guidance of the IBP. The factorization of the variables was conducted using the factor analysis. Using Varimax normalized rotation initial coordinative system were transformed to obtain simple structure of the factors. According the Guttmann Kaiser criterion four significant factors were extracted. Factor scores are calculated for each respondent and each categorized group on each extracted factor. A one-way analysis of variance (ANOVA) with Tukey HSD post-hoc test was used to determine possible significant differences among positions on four extracted factors. The level of significance was set at 0.05. Obtained results confirm the hypothesis of the existence of significant differences in the area of anthropometric characteristics considering positional roles. LDS (Longitudinal dimensionality factor) was identified as the only that significantly differ the groups of volleyball players. A group of central players achieved significantly higher results than all the other groups except the group of diagonal players. The research results indicate that the morphological characteristics of tested groups of volleyball players are similar to those of the other volleyball leagues or national teams which points to valuable potential of tested players. It is interesting that there was no significant difference between the central and diagonal players and the fact is that in most serious volleyball teams central and diagonal players really are the highest ones. This is logical considering the specific assignments of these players during one volleyball match. Obtained informations may serve as a normative values as well as a support in directing players to a specific playing role in order to optimize their situational effectiveness finally reaching an optimal competition results in a sports career.